Monolithic CMUT on CMOS Integration for Intravascular Ultrasound Applications - Zahorian, Jaime (2011)
One of the most important promises of capacitive micromachined ultrasonic transducer (CMUT) technology is integration with electronics. This approach is required to minimize the parasitic capacitances in the receive mode, especially in catheter based volumetric imaging arrays where the elements need to be small. Furthermore, optimization of the available silicon area and minimized number of connections occurs when the CMUTs are fabricated directly above the associated electronics. Here, we describe successful fabrication and performance evaluation of CMUT arrays for intravascular imaging on custom designed CMOS receiver electronics from a commercial IC foundry. The CMUT on CMOS process starts with surface isolation and mechanical planarization of the CMOS electronics to reduce topography. The rest of the CMUT fabrication is achieved by modifying a low temperature micromachining process through the addition of a single mask and developing a dry etching step to produce sloped sidewalls for simple and reliable CMUT to CMOS interconnection. This CMUT to CMOS interconnect method reduced the parasitic capacitance by a factor of 200 when compared with a standard wire bonding method. Characterization experiments indicate that the CMUT on CMOS elements are uniform in frequency response and are similar to CMUTs simultaneously fabricated on standard silicon wafers without electronics integration. Experiments on a 1.6 mm diameter dual-ring CMUT array with a 15 MHz center frequency show that both the CMUTs and the integrated CMOS electronics are fully functional. The SNR measurements indicate that the performance is adequate for imaging CTOs located 1 cm away from the CMUT array.